The Marriage Wage Premium: Does It Exist among Generation Z in Indonesia? - Lestari Agusalim; Khalil Gibran Ramadhan; Efendri Efendri (International Journal of Multidisciplinary Sciences and Arts, 2025)
This study aims to analyze the Marriage Wage Premium (MWP) phenomenon among Generation Z (Gen Z) workers in Indonesia, with a focus on wage differences between those who are married and those who are unmarried. Using data from the National Labor Force Survey for the period of August 2018-2023 published by BPS-Statistics Indonesia, this research employs a logit regression analysis method to explore the impact of marital status on the probability of earning a low wage. The analysis results show that marital status significantly affects the likelihood of earning a low wage, with married workers having a 5.09% higher probability of earning a low wage compared to unmarried workers. Additionally, the analysis reveals that married female workers are more likely to earn a low wage compared to married male workers, with a larger gap observed among women. These findings contradict the classical MWP theory, which asserts that married workers, particularly men, tend to have higher wages. This result suggests that factors such as a more flexible labor market structure, changes in social norms, and the dominance of the informal sector and gig economy may contribute to this phenomenon. Based on these findings, it is recommended that labor policies in Indonesia give more attention to work flexibility and work-life balance, especially for young workers. Programs supporting informal sector workers and policies aimed at reducing gender-based wage disparities are also necessary to create a more equitable labor market for Gen Z.